MODEL BIMBINGAN KARIR UNTUK PEMAHAMAN MINAT PADA SISWA TUNARUNGU SEKOLAH MENENGAH ATAS LUAR BIASA - Endang Pudjiastuti Sartinah (Department of Special Education, 2014)
This study aims to develop a model for understanding the interest of career counseling for deaf students SMALB-B. Procedure development in this study adapt the model development Borg & Gall. Acceptability testing procedures models of career guidance is done through (1) test expert Counseling and Special Education expert, the data from the test were analyzed descriptively experts qualitatively and quantitatively by using descriptive statistics, (2) main field trials or small-scale, data from the field test analysis using statistical techniques Paired Samples T test. From the test results show that the model expert career guidance for understanding the proper interest for deaf students, useful and feasible, and can be used in providing career guidance services for deaf students. While the results of a limited field test shows the results of the analysis of data from different test the skills to understand the interest in showing the value of t = -51.137 which falls on the significance of 0.000 (<0.05). This means that there are differences in understanding the skills of deaf students’ interest SMALB-B before and after participating in career guidance for understanding interest. This means that the change in the level of interest, especially in optimizing understanding changes in student knowledge and skills SMALB-B.Penelitian ini bertujuan untuk mengembangkan model bimbingan karier untuk pemahaman minat bagi siswa tunarungu SMALB-B. Prosedur pengembangan dalam penelitian ini mengadaptasi model pengembangan Borg & Gall. Prosedur pengujian akseptabilitas model bimbingan karir ini dilakukan melalui (1) uji ahli Bimbingan Konseling dan ahli Pendidikan Luar Biasa, data dari uji ahli dianalisis secara deskriptif kualitatif dan kuantitatif dengan menggunakan statistik deskriptif, (2) uji coba lapangan utama atau skala kecil, data dari uji lapangan di analisis dengan menggunakan teknik statistik uji Paired Samples T Test. Dari hasil uji ahli menunjukkan bahwa model bimbingan karier untuk pemahaman minat bagi siswa tunarungu tepat, berguna dan layak serta dapat digunakan dalam memberikan layanan bimbingan karier bagi siswa tunarungu. Sedangkan dari hasil uji lapangan terbatas menunjukkan hasil analisis data dari uji beda keterampilan memahami minat menunjukkan nilai t = -51,137 yang jatuh pada signifikansi 0,000 (< 0,05). Artinya ada perbedaan keterampilan memahami minat siswa tunarungu SMALB-B sebelum dan sesudah mengikuti bimbingan karier untuk pemahaman minat. Artinya adanya perubahan tingkat pemahaman minat terutama dalam mengoptimalkan perubahan pengetahuan dan keterampilan pada siswa SMALB-B.